Obraz ponowoczesnego świata z perspektywy współczesnej młodzieży - Myszka, Uniwersytet im. Adama Mickiewicza w Pozn Lucyna (Kultura-Społeczeństwo-Edukacja, 2014)
Modern reality is ambivalent, heterogenous, ambiguous and unpredictable. The living conditions it creates aren’t easy for adolescing people forced to realize many developmental tasks. Among theese tasks is forming a mature vision of reality. This article presents the postmodern view of the world from the perspective of young people, based on research conducted on high school graduates. It shows young people as very reflective, critical towards certain aspects of postmodernity but at the same time, due to highly developed adaptational skills, able to find their place in the world and make use of its possibilities.